Conversion of protein-rich lignocellulosic wastes to bio-energy: Review and recommendations for hydrolysis + fermentation and anaerobic digestion. (August 2021) - Cheng, F.; Brewer, C.E.
Abstract: Considerable amounts of organic waste materials are disposed of in landfills or by incineration, creating the potential for environmental problems and missing opportunities for energy and material applications. The more digestible, valuable, and edible components (e.g. starch, lipids, edible fibers, and essential proteins for human health) are generally extracted first from biomass feedstocks, leaving the more recalcitrant, less beneficial, and unpleasant components. Due to higher-cost extractions, immature conversion techniques, and lower market demand, lignin and protein can become enriched in these biomass wastes: agricultural residues, dedicated (biofuel) plants, distillers' grains, seed cakes, forestry residues, food wastes, municipal solid wastes, sewage sludges, and digestate solids. These protein-rich lignocellulosic wastes still contain abundant fibrous polysaccharides (e.g. cellulose and hemicellulose) that have the potential for (further) conversion. In this review, each waste feedstock is evaluated for valorization by hydrolysis + fermentation, and anaerobic digestion, based on biomass composition, biomass degradation mechanisms, and yield/quality of the end products. Agricultural residues, dedicated plants, and distillers' grains have the highest bioethanol yields compared to the other feedstocks. Stillage, sewage sludge, municipal solid waste, de-oiled seed cakes, and food wastes show higher activities in anaerobic digestion and produce greater biogas yields. Integration of hydrolysis + fermentation and anaerobic digestion may maximize the bioenergy recovery, and minimize residue generation, from most types of protein-rich lignocellulosic wastes. Screening wastes for different conversion methods enables greater chances for profitability while mitigating environmental risks within agricultural, industrial, and municipal sectors. Highlights: Agricultural residues, dedicated plants, and DDGS favor ethanol production. Stillage, sewage sludge, seedcakes, and food wastes favor methane production. Serial integration of conversion methods maximizes feedstock utilization value.